Analisis Tingkat Pemahaman Mahasiswa Jurusan Kesehatan UMS Terkait Penggunaan Obat Bebas dan Obat Bebas Terbatas Untuk Swamedikasi - Alida Rahmalia Damayanti; Mufida Alfiana; Monica Edelwais; Farah Qanitha Zulfa; Muhammad Labib Qotrun Niam (Jurnal Penelitian Farmasi & Herbal, 2023)
Self medication is an effort to carry out treatment independently. The implementation of self medication must be based on knowledge about self medication itself, one of which is regarding the use of over the counter and limited over the counter drugs. Students majoring in health as potential to be health workers must have a good level of understanding regarding the use of over the counter and limited over the counter drugs in order to provide education to the general public so it can reduce the risk o medication error. The study was conducted using a cross sectional method by collecting primary data from the result of a questionnaire which was then filled out by 78 respondents who were the students majoring in health at the Muhammadiyah University of Surakarta. The research instrument used was tested for its validity and realibility using the SPSS version 16.0 program. From the validity and reliability tests, 10 questions were valid and the insrument used were reliable. Based on the research conducted, it was found that students majoring in health at the Muhammadiyah University of Surakarta have a sufficient level of understanding regarding to the use of over the counter and limited over the counter drugs for self medication with an average score of 68,08.